Religiositas dan Stres Menghadapi Ujian Nasional pada Siswa Sekolah Menengah Umum - Belladina Aulina; Fuad Nashori (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2012)
The purpose in the research is to understand the correlation between religiosity and stress ahead of national exam in high school students. The hypothesis of this research is that there is negative correlation between religiosity and the stress ahead of national exams in high school students. The higher the religiosity, the lower stress ahead of the national exam. The lower the religiosity, the higher stress ahead of the national exam. Subjects of this research were students of the 3rd grade of high school. This research used the religiosity scale which is arranged by the researcher, based on the dimensions of religiosity according to Glock and Stark (Ancok & Suroso, 2008) and the stress scale, based on the theory of Sarafino (1994). Method of this research was used to verify the negative correlation between religiosity and stress ahead a national exam in high school students. Product moment correlation of Pearson shows the value of r = - 0.176 with p = 0.040 (p < 0.05), which means that there is a significant negative correlation between religiosity and stress ahead of national exams in high school students, thus the hypothesis is accepted.Key words: Religiosity, stress ahead of the national exam